Algunas consideraciones económicas (1836). Análisis mexicano de la depresión a principios del siglo XIX - Salvucci, Richard J. (El Colegio de México, A.C., 2005)
Algunas consideraciones económicas, published anaonymously in Mexico in 1836, offers a remarkably modern  analysis of the depression  of the early nineteenth century.  Internal evidence suggests its author was Jose Mariano Michelena, who negotiated the Mexican loan with  Barclay,  Herring and  Richardson, and whose personal fortunes  suffered many of the reverses of which the  pamphlet  speaks. A fixed exchange rate, irreducible  costs, and the wealth effect of declining rural property values had de- pressed total demand.  The author  recommends a currency  that abandons  fixed parity with silver and brings an end to deflationary pressures,  but maintains  its value by monetizing the liabilities tied to the real wealth of estate owners.